Cultivos intercalares em fase inicial de desenvolvimento e desempenho produtivo de cultivares de palma de óleo em diferentes ambientes de Roraima - Lopes, Antonia Dianaia Oliveira (2014)
The expansion of oil palm cultivation in already deforested areas of Amazonia is recognized as an excellent alternative for the production of oil for food and energy purposes. The state of Roraima has the appropriate environmental conditions for its development and introduction in the structure of family farming. The objective of this work is to develop systems of crops between the rows of oil palm in an area of disturbed forest, during the initial period of development of culture, as well as evaluate the productive potential of three intraspecific varieties of oil palm in areas of savanna and forest changed from Roraima. To achieve the objectives were different and conducted experiments in areas of disturbed forest and savannah of Roraima. For intercropping systems with cultivation of palm oil had a randomized block design with three replications, and treatments for the compounds: palm oil x banana x cowpea; palm oil x pineapple; palm oil x cassava; oil palm x cowpea x maize; oil palm x cassava x maize; oil palm x cowpea; oil palm x peanuts and palm oil in single system. For the productive performance of three cultivars of palm oil had a randomized with six replications and three treatments in two blocks environments. In the first experiment evaluated the vegetative development of oil palm through the girth circumference, 9 leaf length, width and thickness of the rachis, number of leaflets leaf 9 and number of leaves per plant issued at 2:18 months after planting ( site A) and at 12 and 28 months after planting (Site B) . Moreover, evaluations of BRS C - 2528, 1 BRS C - 370 and BRS C - 2301 of oil palm joint analyzes of the periods 4-6 years old , as the number of clusters ha-1 were performed, weight average and total production of ha-1 clusters. We conclude that systems favored the vegetative growth of the crop of oil palm were the cowpea intercropping systems with x maize, groundnuts and cassava, proving to be economically viable and may also be indicated as a cheap alternative for the production of palm oil facing family farmers. Cultivars of oil palm in the disturbed forest environment, showed higher than in the savanna environment productive performance.